2002
DOI: 10.1089/109493102753685854
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and Auditory Virtual Environments: Affect-Based Judgments of Music Reproduced with Virtual Reverberation Times

Abstract: Emotions are experienced both in real and virtual environments (VEs). Most research to date have focused on the content that causes emotional reactions, but noncontent features of a VE (such as the realism and quality of object rendering) may also influence emotional reactions to the mediated object. The present research studied how noncontent features (different reverberation times) of an auditory VE influenced 76 participants' ratings of emotional reactions and expressed emotional qualities of the sounds. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
5
36
2
1
Order By: Relevance
“…For Heroic, Large Hall Back was ranked significantly greater more often than all the other options combined. This result is in contrast to that found by Västfjäll [45] and Tajadura-Jiménez [46] since Heroic, like Happy, is also high-Valence, and they would have predicted that Heroic would have had a similar result as Happy. Table 4 also shows that Anechoic (and to a lesser extent Small Hall Front and Large Hall Front) was the most Comic, while Large Hall Back was the least Comic.…”
Section: Ranking Results For the Emotional Characteristics With Diffecontrasting
confidence: 92%
See 3 more Smart Citations
“…For Heroic, Large Hall Back was ranked significantly greater more often than all the other options combined. This result is in contrast to that found by Västfjäll [45] and Tajadura-Jiménez [46] since Heroic, like Happy, is also high-Valence, and they would have predicted that Heroic would have had a similar result as Happy. Table 4 also shows that Anechoic (and to a lesser extent Small Hall Front and Large Hall Front) was the most Comic, while Large Hall Back was the least Comic.…”
Section: Ranking Results For the Emotional Characteristics With Diffecontrasting
confidence: 92%
“…5 indicates that Happy is high-Valence or very pleasant). The result also agrees with Västfjäll [45], who found that larger reverberation times were more unpleasant than shorter ones. For Heroic, Large Hall Back was ranked significantly greater more often than all the other options combined.…”
Section: Ranking Results For the Emotional Characteristics With Diffesupporting
confidence: 91%
See 2 more Smart Citations
“…However, incorporating real-time updated 3D sound to VR technologies addresses several practical issues. If there is a consensus on the fact that presence is improved by 3D sound, little is known about how an auditory VE should be designed so that it does not interfere with the visual VE (Vastfjall, Larsson, & Kleiner, 2002) but enhances the sensorial realism of the simulation. In a previous experiment involving navigation within a visual and auditory VE, several patients with agoraphobia reported that the auditory and visual worlds could not fulfil a sense of realism when presented together (Viaud-Delmon, Warusfel, Seguelas, Rio, & Jouvent, 2006).…”
Section: Discussionmentioning
confidence: 99%